2004
DOI: 10.1097/00005537-200410000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Bone Fractures: Traditional Classification and Clinical Relevance

Abstract: Traditional temporal bone fracture descriptions correlate poorly with clinical findings. However, simply distinguishing petrous from nonpetrous involvement demonstrates significant correlation with the occurrence of serious sequelae of temporal bone fractures. Subcategories of mastoid and middle ear involvement further refine this classification schema to correlate with minor complications. This simple, radiographically based scheme better focuses clinical resources and attention toward more likely sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
116
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(134 citation statements)
references
References 13 publications
16
116
0
2
Order By: Relevance
“…Thus, if the fracture line reaches those organs, it may induce sensorineural hearing loss [4], CSF otorrhea, or facial nerve paralysis [5,6]. According to a classification based on petrous bone involvement, Ishman reported that petrous bone fractures result in ten times greater likelihood of CSF leak and three times greater likelihood of facial nerve injury compared with non-petrous bone involvement [2]. Thus, it is important to identify where the fracture line ends, particularly when it is directed toward the critical organs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, if the fracture line reaches those organs, it may induce sensorineural hearing loss [4], CSF otorrhea, or facial nerve paralysis [5,6]. According to a classification based on petrous bone involvement, Ishman reported that petrous bone fractures result in ten times greater likelihood of CSF leak and three times greater likelihood of facial nerve injury compared with non-petrous bone involvement [2]. Thus, it is important to identify where the fracture line ends, particularly when it is directed toward the critical organs.…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic factors of traumatic facial palsy are the severity and onset time of facial nerve paralysis. Incomplete and delayed types of facial nerve paralysis present a better prognosis [2,9]. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance treatment quality, TBTs radiographic features should be depicted according to the involvement of all temporal bone components and its potential clinical implications, as recently stressed in the literature [4,5].…”
Section: Conclusive Proposalmentioning
confidence: 99%
“…One among most compelling system considers whether the otic capsule structures have been violated or spared. Otic capsule violating fractures have been reported to have a higher incidence of loco-regional complications [4,8].…”
Section: Conclusive Proposalmentioning
confidence: 99%